ROMANIA'S EXTERNAL MIGRATION FROM THE PERSPECTIVE OF ACCESSION TO THE EU - INSTITUTIONAL AND BEHAVIOURAL CHALLENGES - Daniela-Luminita Constantin; Luminita Nicolescu (European Regional Science Association (ERSA), 2005)
This paper represents a part of the authors' contribution to a study developed under the auspices of the European Institute in Romania included in the "Pre-Accession Impact Studies - PAIS II” series, funded by a Phare project. The study combines the aspects related to mechanisms, legislation, institutional and behavioural challenges with the quantitative and qualitative estimations of the external migration effects, in accordance with Romania's preparations for accession to the EU. The main conclusion pointed out by the analysis of the institutional issues is that so far the measures which are adopted in Romania with regard to both legislation and institutional framework are rather reactive, aiming to ensure the adjustment to the EU requirements, than to design and follow a national migration policy with clear objectives. As it completes the creation of the legal-institutional framework according to the EU standards, Romania will concentrate on designing its own migration policy, convergent with those existing at European level. Moreover, the elaboration and adoption of laws, the creation of institutions, the development of corresponding strategies and policies represent major components of this process, but their success cannot be separated from the manner in which the involved actors –governmental institutions, non-governmental organizations, mass-media, communities, individuals – respond to the so-called "behavioural challenges”, related to participation, communication, mentalities and attitudes. The paper is organized as follows: first, an analysis of the integration mechanisms is provided, focusing on migration flows, specific mechanisms and institutional-legislative framework created in Romania for external migration administration. Second, the inquiry into the social-cultural dimension highlights the migrant's profile (emigrant, immigrant), the issues related to the integration within the host country and the phenomenon perception by public opinion and mass-media. The entire paper supports the idea that with a careful, objective vision and proper management the future national migration policy may become a major catalyst, able to enhance a new economic prosperity in Romania.
Keywords: 330